The Department of Education Computerization Program (DCP): Evaluating its Effectiveness and the Challenges Faced by Public Schools - Norveen S. Campanilla; John David B. Medrano (Goodwood Publishing, 2026)
Purpose: This study aimed to evaluate the overall impact and effectiveness of the DepEd Computerization Program (DCP) in enhancing the educational experience, identifying challenges, and understanding the factors influencing its successful implementation in schools. Research Methodology: The study evaluated the effectiveness of the DepEd Computerization Program using a mixed-methods approach, combining quantitative survey data from school ICT coordinators with qualitative insights from interviews and focus groups, identifying areas of consensus and divergence. Results: The DepEd Computerization Program significantly enhanced the quality of education by integrating ICT into teaching and learning and improving ICT literacy among learners, teachers, and school heads. However, challenges such as broken outlets and inadequate ventilation pose safety risks and limit the program effectiveness. To sustain and further enhance the program, continuous ICT training, skill development, and better maintenance of infrastructure are essential. Conclusions: The DepEd Computerization Program is highly effective in improving teaching, learning, and ICT literacy. Despite minor infrastructure challenges, continuous training and maintenance are essential to sustain its long-term impact. Limitations: The study evaluates the overall impact and effectiveness of the DepEd Computerization Program (DCP) in enhancing the educational experience, identifying challenges, and understanding the factors influencing its successful implementation, particularly in schools in Allacapan and Aparri Districts. Contributions: Based on the study's findings and conclusions, it is recommended that the Department of Education (DepEd) and the DCP organize continuous training for educators and involve the community in fostering a supportive environment for ICT integration in the classroom. Additionally, schools should establish regular maintenance schedules for ICT equipment, enhance teaching practices with interactive approaches, and collaborate with other institutions.